A case of subcapsular renal hematoma status post celiac artery thrombectomy. (April 2021) - Iskander, Peter
Highlights: Proper visualization of all vascular structures should be done prior to any interventions. Care should be taking while performing procedures to avoid excessive force. All vessels should be well inspected after any procedure is completed to monitor for any bleeding damage. Patients should be continuously monitored for signs of complications. (infection/bleeding/swelling). Abstract: Introduction: 30 year old male with no significant past medical history presenting to the hospital with significant left-sided abdominal pain. Case presentation: Patient was found to have a thrombus within the celiac artery for which he underwent a catheter assisted thrombolysis procedure. Hypercoagulable work-up revealed evidence of a JAK 2 V617F mutation which is indicative of Polycythemia Vera. The patient returned the following day with considerable left-sided flank pain associated with shortness of breath, nausea, and vomiting. CT performed showed evidence of an expanding left renal subcapsular hematoma. Patient was treated conservatively with IV fluids and pain medication before he was discharged hemodynamically stable after a few days. Discussion/conclusion: Accessory renal vessels can be a rare finding coming of the celiac artery and so, care must be taken to evaluate vascular anatomy to avoid iatrogenic injuries; a bleed from one of these vessels could lead to the development of a hematomas, as seen with this patient.